Catalogue of the type material in the entomological collection of the Natural History Museum of Denmark: basal hexapods - Eusébio, Rita; Sendra, Alberto; Enghoff, Henrik; Reboleira, Ana Sofia P.s. (Zootaxa, 2018)
A catalogue of type specimens of basal hexapods (Collembola, Protura, Diplura, Archaeognatha, Zygentoma) in the collection of the Natural History Museum of Denmark, University of Copenhagen is presented. The NHMD collection harbours type material of 175 species, and it is composed of 132 holotypes, 4 neotypes, 3 syntypes, 32 lectotypes, and 39 paratypes. For Diplura one neotype is newly designated. The order Protura is represented by 5 families, Collembola by 7 families, Diplura by 6 families, Archaeognatha by 1 family and Zygentoma by 2 families.